Boundedness of Commutators for Marcinkiewicz Integrals on Weighted Herz-Type Hardy Spaces (Analysis in Theory and Applications, 2011)
In this paper, the authors study the boundedness of the operator $μ^b_Ω$, the commutator generated by a function $b \in \text{Lip}_β (R^n)$ $(0
Keywords: Marcinkiewicz integral; commutator; weighted Herz space; Hardy space.